Male seminal parameters are not associated with Leydig cell functional capacity in men. (24th March 2021) - Anand‐Ivell, Ravinder; Tremellen, Kelton; Soyama, Hiroaki; Enki, Doyo; Ivell, Richard
Abstract: Background: Insulin‐like peptide 3 (INSL3) is a constitutive, secreted peptide produced in the male uniquely by the Leydig cells of the testes. It is a biomarker for Leydig cell functional capacity, which is a measure of the numbers and differentiation status of these steroidogenic cells and lacks the biological and technical variance of the steroid testosterone. This retrospective study was carried out to examine the relationship between seminal parameters and the Leydig cell compartment, and secondarily to assess other factors responsible for determining Leydig cell functional capacity. Methods: INSL3 was assessed together with seminal, anthropometric, and hormonal parameters in a Swedish cohort of 18‐year‐old men, representing the average population, and in a smaller, more heterogeneous cohort of men visiting an Australian infertility clinic. Results and discussion: Average INSL3 concentration at 18 years is greater than that reported at younger or older ages and indicated a large 10‐fold variation. In neither cohort was there a relationship between INSL3 concentration and any semen parameter. For the larger, more uniform Swedish cohort of young men, there was a significant negative relationship between INSL3 and BMI, supporting the idea that adult Leydig cell functional capacity may be established during puberty. In both cohorts, there was a significant relationship between INSL3 and FSH, but not LH concentration. No relationship was found between INSL3 and androgen receptor trinucleotide repeat polymorphisms, reinforcing the notion that Leydig cell functional capacity is unlikely to be determined by androgen influence alone. Nor did INSL3 correlate with the T/LH ratio, an alternative measure of Leydig cell functional capacity, supporting the view that these are independent measures of Leydig cell function.